Controle biológico e alternativo da cochonilha (Phenacoccus manihoti Matile-Ferrero) na cultura da mandioca (Manihot esculenta Crantz) - Rheinheimer, Ana Raquel (2010)
This study aimed to evaluate the action of entomopathogenic fungi and plant protection products used in alternative agroecological on nymphs of P. manihoti in cassava. The four upper leaves of cassava plants infested with nymphs of the mealybug P. manihoti application of treatments received in the lower surface of leaves on the nymphs, using a spray nozzle attached to an air compressor. After application, the plants were kept in semi-conditioned room (temperature 25 ± 5 º C and a photoperiod of 12h) and other insects on the leaves with the aid of prepared leaf cages per screen anti-aphids. The pesticides were evaluated by the insect mortality at 3, 5, 7 and 9 days after application. The mortality caused by strains of entomopathogenic fungi and commercial insecticides on nymphs was assessed daily for 10 days. For confirmation of death by the pathogen, the bodies were immersed in 70% alcohol and then in distilled water, transferred to Petri dishes and maintained at temperature (26 ± 1 ° C and a photoperiod of 14 hours). It was observed that all pesticides tested on nymphs proved efficient when the final assessment, however, differ in the mortality rate, and the products Pironim®, Lime sulfur®, Compostonat® and Plant Clean® presented the efficiency causing at least 50% mortality of nymphs of P. manihoti. Among isolates tested, only three were pathogenic to P. manihoti causing the corrected mortality varied from 15,2 to 28.5%, following 10 days of application. The other isolates tested showed low activity or were not pathogenic to Scale. The commercial biopesticides based on fungi were pathogenic to the nymphs of P. manihoti, causing mortality of 10 to 45.8%, and the best result was obtained with the product based on B. bassiana (Bovenat®) which provided 45.8% mortality confirmed